IMMUNOLOGICAL EVOLUTION OF A COHORT OF HIV-2 INFECTED PATIENTS: PECULIARITIES OF AN UNDERESTIMATED INFECTION - Emanuele Focà; Benedetta Fumarola (Mediterranean Journal of Hematology and Infectious Diseases)
"IMMUNOLOGICAL EVOLUTION OF A COHORT OF HIV-2 INFECTED PATIENTS: PECULIARITIES OF AN UNDERESTIMATED INFECTION"